Da festa da chegada ao carnaval itinerante : uma abordagem fotoetnográfica sobre o Maracatu de Baque Solto Cambinda Brasileira - Freire, Paulo Airton Maia (2021)
This research work was an empirical study reference about the “Cambinda Brasileira”, a Rural maracatu group, from Nazaré da Mata municipality, Pernambuco State. Among the various festivities held by Maracatu, we realized the "festa da chegada" as the most important one. It takes place on Carnival Sunday presentations. This celebratory act prepares the players for the following Carnival days. There are many characters that are part of the celebration, among then, the "caboclo de lança" had an important place of my attention and reflection. With his performances, he synthesizes the joy and constant resistance that mark the history of the Zona da Mata of Pernambuco state, where my research work took place. We will study, in this work about how this character expresses some aesthetic, corporal and social elements. With the purpose of showing the relationship between body, festival and visualities, we started from two fundamental point of views: the perspective of the festival, in accordance with the anthropological theories about festivals; and the Luiz E. R. Achutti “photoethnography” comprehension, to deal with the ritualized body of the “caboclo de lança” that incorporates diverse daily narratives of resistance, fight, creativity, exploration of his work, mysteries and festivities. It was the perspective that led me to build a visual narrative about the Maracatu.